Plan de marketing educativo para captar y fidelizar alumnos en la institución educativa Nº 81534 “Iris Barriga Galarreta” de Chiquitoy, 2017 - Barros Benites, Yen Mari (2023)
The objective of this research was to design and implement an educational marketing plan to increase the recruitment and loyalty of students in the Educational Institution No. 81534 "Iris Barriga de Galarreta" in Chiquitoy. It presents a descriptive-proposal design. The sample consisted of parents because they decide the enrollment of their children. The instrument used was the questionnaire. For the collection and analysis of the information, descriptive statistics, Spss18, Excel 2010 was used. The results in the recruitment of enrolled students show a low average growth rate of 0.02% during the period 2011 to 2017. In loyalty, it presents an average level of 55%, due to the lack of involvement of the teaching staff, parents, lack of student information and lack of communication. Given this, a comprehensive strategy was proposed that considers the student as the center of attention, teaching commitment, involvement of parents, educational community, having an educational project that responds to the needs and grants differentiated value to families and community in addition to build and disseminate promotion and communication strategies for the activities carried out by the educational institution. Therefore, it is concluded that educational marketing strategies must be implemented to increase the recruitment and loyalty of students in the Educational Institution.